African Union Great Green Wall Initiative Strategy and Ten-Year Implementation Framework (2024-2034): Monitoring, Evaluation, Learning and Adaptation - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This brief presents the proposed Monitoring, Evaluation, Learning, and Adaptation (MELA) approach for the revised African Union Great Green Wall Initiative (GGWI) Strategy and Ten-Year Implementation Framework (2024–2034). The MELA framework is central to ensuring adaptive design, implementation, and continuous improvement of GGWI actions across scales. It emphasizes the need for dedicated planning, adequate resourcing, and robust learning processes to support large-scale landscape restoration and livelihood resilience. The brief highlights the key components of the MELA approach - the development of a multi-scale, comparable scorecard to track progress and a biennial reporting process. It further describes how progress will be monitored through changes in ecosystems, institutions, policies, and community well-being. Learning and reflection are positioned as integral to adaptive management, with mechanisms for local, subnational, national, and continental learning loops.